Spotlight on Technology: Development of an Autonomous Aquarium System for Maintaining Deep Corals - Alejandro Olariaga; Andrea Gori; Covadonga Orejas; Josep-Maria Gili (Oceanography, 2009)
Keeping deep corals alive under optimum water temperature and quality conditions is not an easy task. It is important to achieve a balance among a high-water renewal rate, constant water temperature, flow speed, and nutrient concentrations (especially ammonium). In trying to find a "meeting point" among all of these factors, the ZAE (Experimental Aquaria Area) of the Instituto de Ciencias del Mar (CSIC) in Barcelona developed an aquarium system that maintains constant temperature conditions in an open water circuit for five deep coral species being kept for HERMES project experimental purposes (Figure 1). The new system operates with a temperature variation of ± 0.2°C, allowing culture conditions similar to those in the field.